Study of the Existence of the Toba Pyramid Site in Marbun Toruan Village Using a Combination of Geoelectric and Satellite Imagery Methods - Olihta Kudadiri; Rahmatsyah; Rita Juliani; Juniar Hutahean; Muhammad Kadri; Togi Tampubolon (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
There has been research studies on the existence of the Toba Pyramid Site with the aim of finding out the subsurface rock structure. Measurements were made using ARES D4 v.47, SN: 06091345. ARES data is processed using Res2Dinv software. The results of geoelectric research show that the resistivity varies from 500 Wm to 3000 Wm estimated as alluvium, sand, gravel, dry gravel, and tuff. In addition to using Res2Dinv software, the data was also processed using surfer 13 software to obtain variations in specific gravity at depths of 5m, 10m, and 15m. In addition to using geoelectric methods, Landsat 8 OLI and USGS DEM satellite images were also used to obtain rock types at the research site. The results of the image interpretation show that the rock types of the study area are tuff and alluvium. This shows that the results of geoelectric and image interpretation are in accordance with the geological map of Marbun Toruan Village.